2015
DOI: 10.1016/j.brainres.2015.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of astrocytes and T cells in physiological and pathological conditions

Abstract: The central nervous system (CNS) has long been recognized as a site of ‘immune privilege’ because of the existence of the blood brain barrier (BBB) which presumably isolates CNS from the peripheral immunosurveillance. Different from the peripheral organs, CNS is unique in response to all forms of CNS injury and disease which is mainly mediated by resident microglia and astrocyte. There is increasing evidence that immune cells are not only involved in neuroinflammation process but also the maintenance of CNS ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 145 publications
0
63
0
2
Order By: Relevance
“…For example, astrocyte-secreted CXCL10 promotes the recruitment and entry of lymphocytes into the CNS, and worsens acute spinal cord demyelination in EAE (56, 57). Indeed, there is a growing appreciation for astrocyte-T cell interactions (5860). The impact of CNS-resident CD8 T cells on astrocyte functions in aged brains remains to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, astrocyte-secreted CXCL10 promotes the recruitment and entry of lymphocytes into the CNS, and worsens acute spinal cord demyelination in EAE (56, 57). Indeed, there is a growing appreciation for astrocyte-T cell interactions (5860). The impact of CNS-resident CD8 T cells on astrocyte functions in aged brains remains to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…Blood-brain barrier (BBB) leakage contributes significantly to the progression of secondary brain injury after ischemic stroke 1 . Although the primary substrate of BBB injury may involve dysfunction in tight junction proteins within the affected endothelium, emerging data now suggest that gliovascular interactions may also be important.…”
Section: Introductionmentioning
confidence: 99%
“…While it is now accepted that PD is a results of an inflammatory episode and subsequent microglia activation, increasing loss of functioning dopaminergic neurons [34], synthesis and release of multiple cytokines, accumulation of toxic substances, subcellular organelle dysfunction and increased effects of invading cells, a loss of BBB integrity, vascular endothelium integrity and astrocyte damage, are strongly implicated in a continuing loss of protective abilities [7,[35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The same can be said for astrocytes, with 'misplacement' of the cells in PD and Alzheimer's disease and their release of deadly molecules [39]. Thus, protective cells can become harmful during inflammatory episodes and, coupled with an influx of immune cells, causes disruption of the BBB which is exacerbated by usually beneficial astrocytes that are mechanistically altered and interact with invading cells [37][38][39][40]. Indeed, our previous research has shown cuffs of T-cells around vessels after endotoxin treatment, as well as ubiquitin and TNFα in vascular endothelial cells, suggesting that perivascular disruption occurs and that cells respond in both self-preservation and destructive manners [5,43].…”
Section: Discussionmentioning
confidence: 99%